SIKAP WARGA PESANTREN TENTANG FENOMENA RADIKALISME AGAMA - Dilan Imam Adilan (TEMALI : Jurnal Pembangunan Sosial, 2018)
This study focuses on the views and attitudes of Pesantren residents about the religious radicalism-fundamentalism phenomena in two tahfiz (Qur’anic memorized) pesantrens in Bandung. This descriptive-analytical study employs data collection through interviews, document research, and observation. The result of the study is that about the relationship between views and attitudes, the two pesantren citizens carried a moderate paradigm. They tend to try to integrate views that are antagonistic in looking at Islamic relations and social issues. Also they wanted to soften the conservative paradigm that is the light of religious fundamentalism-views and attitudes, which often make a generalization that Islam has opinion that is inseparable from the modernization and progress of the times.